2012
DOI: 10.1159/000342701
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Findings in Breast Reduction Specimens: Detection of Occult Premalignant and Cancerous Lesions

Abstract: Background: As reduction mammaplasty has become one of the most popular reconstructive procedures, there is an increasing number of reports regarding histopathologic findings in breast tissue yielded by the procedure. Patients and Methods: This study evaluates histopathologic findings in breast tissue removed during reduction mammaplasty procedures performed during a 40-month period (2008–2011), and includes 300 patients of which 258 underwent bilateral breast reduction (group B) and 42 unilateral reduction fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previous single‐center studies report rates of occult breast carcinoma in reduction mammaplasty specimens to occur 0.4–1.1% of the time [4, 15, 21–26], with slightly higher rates up to 2.4% when patients with a personal history of breast cancer were included in the study cohort [3, 27–29]. Based on the heterogeneity of patient age, inclusion criteria, pathology sampling practices, and sample size of single‐center cohorts, slight differences in the incidence of occult breast cancer found in breast reduction specimens are to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Previous single‐center studies report rates of occult breast carcinoma in reduction mammaplasty specimens to occur 0.4–1.1% of the time [4, 15, 21–26], with slightly higher rates up to 2.4% when patients with a personal history of breast cancer were included in the study cohort [3, 27–29]. Based on the heterogeneity of patient age, inclusion criteria, pathology sampling practices, and sample size of single‐center cohorts, slight differences in the incidence of occult breast cancer found in breast reduction specimens are to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study Kyriopoulos and colleagues found benign pathologic changes including atypical mild ductal hyperplasia, fibrocystic changes, adenosis, fibro adenoma, and lobularatrophy was found in 67/4% of the patients who underwent bilateral reduction mammoplasty. The prevalence of occult carcinoma was also observed in 1/55% of patients [11]. In another retrospective study by Clark and colleagues incidence of benign and pre-cancerous lesions in breast reduction samples over a period of 5 years was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Elsewhere breast cancer in reduction mammoplasty specimens has been reported in the literature to vary between 0.1% and 4.5%. (2) The patients usually complain of upper backache, of problems in obtaining brassieres of the correct size and finding clothes that fit. They also complain of difficulties in participating in sports.…”
Section: Introductionmentioning
confidence: 99%